GAYA KEPEMIMPINAN, MOTIVASI, DISIPLIN KERJA, KOMPETENSI DAN BUDAYA ORGANISASI TERHADAP KINERJA PERANGKAT DESA DI KECAMATAN ANDONG KABUPATEN BOYOLALI (JURNAL DIMENSI, 2021)
This study aims to determine the influence of the variable leadership style, motivation, work discipline, competence and organizational culture on the performance of village officials in Kecamatan Andong Kabupaten Boyolali.This research method uses a quantitative descriptive research design. The population in all employees who work in Kecamatan Andong Kabupaten Boyolali, amounting to 139 people. The sampling technique used in this study was purposive sampling technique with the number of samples in the study were 57 people or respondents. Data collection using a questionnaire. The data analysis technique used statistical analysis, namely, multiple linear regression test, model feasibility test, hypothesis testing, and the coefficient of determination.The results showed that leadership style, motivation, work discipline, competence and organizational culture had an effect on the performance of village officials in Kecamatan Andong Kabupaten Boyolali. The variable that the leadership style, motivation, work discipline, competence and organizational culture affect the performance of village officials by 0.697 or 69.7%, while 30.3% is influenced by other variables that are not studied, such as work environment, communication, education and others. Suggestions from this research are that Kecamatan Andong Kabupaten Boyolali, continues to improve the quality of leadership style, motivation, work discipline, competence and existing organizational culture, so that the performance of village officials will also increase and become better than before.